Penerapan Metode Finite State Machine Dalam Game “Stories of Cursed Dungeon” Menggunakan RPG Maker MV - Affan Jaeis Chaniago; Fitri Yanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
RPG Stories of Cursed Dungeon is an rpg-themed game where players will play a character in this game. This game tells of a teenager who wants to find a way to cure his father who is cursed, which makes him have to go to Dungeon City to find a cure for his father's curse. This game uses the RPG Maker MV game engine, by applying artificial intelligence, namely FSM (Finite State Machine). FSM (Finite State Machine) is used in every event created in the game Stories of Cursed Dungeon. Like the creation of missions in the game Stories of Cursed Dungeon which uses three things: Circumstances, Events, and Actions. From the tests that have been carried out from the results of the FSM (Finite State Machine) bolt intelligence in the RPG game "Stories of Cursed Dungeon" the existing mission will run if the player or character from the game has completed the previous mission or received an order from the system.